Radiographic Examination of Third Molar Development for Biological Age Assessment in Java Population, Indonesia - Fitri Rizki Amalia; Arofi Kurniawan (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: The individual age as documented in the birth certificate shall be authorized as a chronologicalage. In several countries, falsification of documents relating to an individual age is becoming a major problem,since it is correlated with monetary, marriage, and education matter. Forensic dentistry works to minimizethe possibility of individual age falsification by studying the tooth developmental stages. The objective ofthis study is to observe the applicability of the third molar development related to the biological age.Materials and Methods: A total of 93 OPG (orthopantomogram) of subjects (16 – 23 years old) from theJava population were involved in this study. Third molar developmental stages of the mandibular wereevaluated using the Demirjian et al. method. The statistical analysis was carried out using IBM® SPSS®Statistics version 23.0 (IBM, Armonk, NY, USA).Results and Conclusion: The result showed that the average Java population reached the final stage at anaverage age of 21 ± 1,39 years in females and 20 ± 1,9 years in males. The present study indicates that thedevelopment of mandibular third molar is slightly earlier in males than in females. Besides, Demirjian’smethod is considered as a reliable method for dental age estimation in the Java population.